Interaction between the predator Xylocoris sordidus and Bacillus thuringiensis bioinsecticides - Santos, Nathalia A. dos; Ramalho, Dagmara G.; Marques, Hortencia M.; Godoy, Joana D. S.; De Bortoli, Caroline P.; Magalhaes, Gustavo O. de [UNESP]; Vacari, Alessandra Marieli; De Bortoli, Sergio A. [UNESP] (Wiley-Blackwell, 2020)
Xylocoris species (Hemiptera: Anthocoridae) are known to occur in various habitats and attack a diversity of agriculturally important prey. Other groups of organisms, such as strains of Bacillus thuringiensis Berliner (Bt) bacteria, also have been extensively studied and applied as biological control agents. The use of these Bt-bioinsecticides in association with predators may be a good strategy in integrated pest management. This work had the objective to study predator behaviour, predatory capacity, and functional response of fifth-instar nymphs of Xylocoris sordidus (Reuter) to eggs of Plutella xylostella (L.) (Lepidoptera: Plutellidae) and Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) treated with one of three commercial Bt-bioinsecticides. The predator presented a type II functional response to untreated P. xylostella eggs (control) and to eggs treated with Agree, whereas the response was type III to P. xylostella eggs treated with Xentari and Dipel. However, on a diet of C. cephalonica eggs the predator displayed a type II response curve on eggs treated with each of the three bioinsecticides, and a type III response on untreated eggs. Bioinsecticides based on B. thuringiensis may be used in association with X. sordidus predators to control lepidopterous pest species.
Keywords: biological control; diamondback moth; consumption rate; functional response; Hemiptera; Anthocoridae; Plutella xylostella; IPM; integrated pest management; biocontrol agent; interference; predatory capacity